1975
DOI: 10.1002/chin.197536405
|View full text |Cite
|
Sign up to set email alerts
|

ChemInform Abstract: SYNTHESIS AND CORONARY VASODILATING ACTIVITY OF 2‐SUBSTITUTED ADENOSINES

Abstract: Ausgehend von den 2‐Halogeninosinen (I) werden durch Acetylierung, Chlorierung mit dem Vilsmeier‐Reagens und Aminierung über (II) und (III) die 2‐Halogenadenosine (IV) hergestellt.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 1 publication
0
3
0
Order By: Relevance
“…None of these impurities are commercially available; thus, no preparation methods have been reported. 7 8 9 In this study, four process-related impurities, 6 , 7 , 8 , and 9 , were identified, synthesized, and characterized. Moreover, the key parameters that influenced their formation were also investigated.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…None of these impurities are commercially available; thus, no preparation methods have been reported. 7 8 9 In this study, four process-related impurities, 6 , 7 , 8 , and 9 , were identified, synthesized, and characterized. Moreover, the key parameters that influenced their formation were also investigated.…”
Section: Resultsmentioning
confidence: 99%
“…The synthesis of compound 7 was performed according to Marumoto et al's method. 8 The reaction mixture was obtained via the degradation of compound 1 . HPLC was used to monitor the reaction, and the reaction mixture was filtered when the reaction was finished.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation